Building resilience to future outbreaks infectious disease risk financing solutions for the Central Asia Regional Economic Cooperation Region
This study provides a review of infectious disease risk financing schemes to draw lessons and recommend solutions for the Central Asia Regional Economic Cooperation (CAREC) member countries.